The Existence of Religious Studies Programs at PTKIN Amid the Progressiveness of Institutional Transformation - Enghariano, Desri Ari; Rambe, Toguan (Jurnal Penelitian Medan Agama, 2025)
This article documents the development and changes in institutional status transfer at PTKIN which are so massive, this shows that the position of PTKIN is so responsive to the demands of the times, so that the transformation from the form of Institute (IAIN) to University (UIN) is a necessity at PTKIN. The position of the religious studies study program which is classified as "quite unpopular" both at UIN North Sumatra Medan and UIN Imam Bonjol Padang has indeed received a less than good response from the community, because it is considered that graduates of the Religious Studies Study Program are considered to have no job prospects in the future. The method in this article uses a descriptive-analytical approach as an effort to explore and clarify the existence of religious studies study programs at PTKIN. The results obtained are policies taken with the aim that religious studies study programs can continue to exist amidst the struggles of the modern world today, including holding promotions to various educational institutions, involving lecturers, students, and using media in promoting religious studies study programs, always committing to maintaining academic quality, making alumni a promotional media, always synchronizing the needs of the job market with the study program's work programs, providing excellent service to students, providing scholarships for underprivileged students.